HUBUNGAN PENGETAHUAN IBU HAMIL TRIMESTER III TENTANG PELAYANAN ANTENATAL CARE DENGAN KETERATURAN PEMERIKSAAN KEHAMILAN - Damayanti, Julia; Tedjasulaksana, Regina; Suindri, Ni Nyoman (ARCHIVE OF COMMUNITY HEALTH, 2024)
Pregnant women need assistance with standard antenatal care. Based on the interviews conducted, out of 10 pregnant women who visited the UPTD Puskesmas Sidemen Karangasem Regency, it was found that seven pregnant women did not know the standard of integrated antenatal care but the pregnancy checks or ANC that were applied were in accordance with the 10T standard. The purpose of this study was to determine the relationship between the knowledge of third trimester pregnant women about ANC services and the regularity of pregnancy checks in the UPTD Working Area of ??the Sidemen Health Center, Karangasem Regency. Collecting research data by questionnaires. Data analysis used univariate and bivariate used the Chi Square test with a significance level of p<0.05. The results showed that the level of knowledge of pregnant women in the third trimester about ANC in the working area of ??the UPTD Puskesmas Sidemen, Karangasem Regency, had good knowledge of 43.8%, had sufficient knowledge of 43.8%, and had less knowledge of 12.4%. Meanwhile, the level of regularity of pregnancy checks showed that 68.8% of respondents carried out regular pregnancy checks and 31.2% of them irregularly. There is a significant relationship between ANC knowledge and regular pregnancy check-ups (p=0.036). Keywords:  Knowledge of Pregnancy Examination, Regular Pregnancy Check Up